Issues and challenges in financing the poor : Lessons learned from Islamic microfinance institutions - Kassim, Salina; Satar, Norizan (2019)
Despite the potentially important role of Islamic microfinance in making Islamic finance an inclusive financial system, the industry is faced with a wide ranging of issues. By analysing the experiences of two major Islamic microfinance institutions (IMFIs), namely Baitul Maal Wa Tamwil (BMT) in Indonesia and Amanah Ikhtiar Malaysia (AIM) in Malaysia, this study aims to learn from their experiences of the issues facing them in financing the poor. The study offers an area of novelty by undertaking a comparative analysis between both institutions in efforts to understand the peculiarities facing each IMFI, unlike the earlier studies which are commonly focusing on a specific IMFI. By employing a thorough review of the available literature, the study finds that human resource and sustainability are the main issues facing both IMFIs. While human resource is the most important factor ensuring success of the microfinance institutions, structural issues such as reliance on subsidies could jeopardise their sustainability. Findings of this study contribute towards providing important inputs for sustainability of the IMFIs as well as enriching the literature in the area of Islamic microfinance institutions.